Death in the New World : cross-cultural encounters, 1492-1800 - Seeman, Erik R. (Early American studies., 2010)
Through a series of engrossing narratives, Death in the New World uses the customs surrounding death among Indians, Africans, and Europeans as a lens through which to examine the cross-cultural interactions in North America and the Caribbean in the three centuries following Columbus.